EMIC wave spatial and coherence scales as determined from multipoint Van Allen Probe measurements. Issue 10 (27th May 2016) - Blum, L. W.; Agapitov, O.; Bonnell, J. W.; Kletzing, C.; Wygant, J.
Abstract: Electromagnetic ion cyclotron (EMIC) waves can provide a strong source of energetic electron pitch angle scattering. These waves are often quite localized, thus their spatial extent can have a large effect on their overall scattering efficiency. Using measurements from the dual Van Allen Probes, we examine four EMIC wave events observed simultaneously on the two probes at varying spacecraft separations. Correlation of both the wave amplitude and phase observed at both spacecraft is examined to estimate the active region and coherence scales of the waves. We find well‐correlated wave amplitude and amplitude modulation across distances spanning hundreds to thousands of kilometers. Phase coherence persisting 30–60 s is observable during close conjunction events but is lost as spacecraft separations exceed ~1 Earth Radii. Key Points: Multipoint Van Allen Probe measurements are used to investigate EMIC wave amplitude and phase correlation at varying spacecraft separations EMIC wave active regions can span Earth radii and persist for hours Phase coherence scales of these waves break down somewhere between a few 100 to few 1000 km